Motivation and interpersonal sensitivity: Does it matter how hard you try? - Hall, Judy; Blanch, D; Hogan, T; Murphy, Nora; Rosip, J; Schmid Mast, Marianne (My University, 2009)
Across 11 experiments, motivation to be accurate on a test of interpersonal sensitivity was manipulated using five methods for increasing motivation (monetary incentive, ego motive, forewarning that accuracy would be tested, exhortation to try hard, and framing the interpersonal sensitivity test description to suggest that performance was gender relevant). Participants were then given an interpersonal sensitivity test consisting of interpreting the meanings of cues or recalling a target person’s appearance, nonverbal cues, or spoken utterances. Neither the individual studies, nor a meta-analysis of the 11 studies, found that the motivation manipulations improved participants’ accuracy on interpersonal sensitivity tests that involved the processing of nonverbal cues. However, motivation had a significant positive effect when sensitivity was defined as recall of verbal cues. There was no evidence that any of the manipulations had a differential impact on men and women.
Keywords: Meta-analysis; Motivation; Interpersonal sensitivity; Accuracy; Nonverbal; Verbal; Gender